Estimation of the Permeability of GFRP Sheet Reinforced Concrete, Under Extreme Environments, Using "Cylindrical Chamber" Method - Mahmood Naderi (Iranian Society of Structrual Engineering (ISSE), 2021)
Nowadays, the glass fiber-reinforced polymer (GFRP) sheets have been known to be one of the most effective composite materials that are used to increase the strength and durability of concrete structures. Owing to the light weight, corrosion resistance, high tensile strength and the ease of application without any interruption of the services, the use of these sheets has become very wide spread. In recent years, some organizations in Iran have opted for the use of GFRP sheets for the strengthening and protection of their concrete structures that are located in the areas exposed to the Persian Gulf water. Therefore, in the present paper, the results of the permeability tests conducted on GFRP strengthened concrete samples, using the newly developed “Cylindrical chamber” method are discussed. Since the deterioration of concrete structures exposed to extreme environmental conditions due to the water penetration, appears to be a critical issue, the above mentioned samples have been exposed to different cycles of wet-dry, high and low temperatures and freeze- thaw tests, before measuring their permeability’s.  The results showed that the temperature change cycles have a small effect on the permeability of GFRP in comparison to the freeze-thaw and wet-dry cycles. The penetrated volume of water after 30, 90, 150 wet-dry cycles, was 61%, 100%, 18% lower than the respective values obtained after the same cycles of temperature changes. Considering the freeze-thaw conditions it was found that similar cycles of freeze-thaw tend to increase the permeability of the samples by about 12%, 36%, 29%, compared with the respective values of the temperature change conditions.